Mortality rate in patients in a long-term psychiatric care facility in Johannesburg - Mokgokong Mathekga; Nokhutula Mdaka; Mvuyiso Talatala (South African Journal of Psychiatry)
Background: Limited research exists on mortality rates and contributing factors among individuals with severe mental illness (SMI) in long-term psychiatric care, especially in low- and middle-income countries (LMICs).